Elaboração de um manual de procedimentos operacionais de um potenciostato/galvanostato para análises eletroquímicas - Félix, Bruna Raquel Bezerra (Universidade Federal Rural do Semi-Árido, 2020)
In view of the difficulty in understanding and handling the galvanostat/potentiostat AUTOLAB model PGSTAT204®, a simplified operations manual was created to assist students and professionals in the electrochemical techniques application. Among the possible techniques that can be performed by the equipment, linear potentiodynamic polarization and electrochemical impedance spectroscopy are included, which describe the behavior and performance of certain materials. The progress of the existing methodological procedure was analyzed and subsequently adjusted according to the guidelines of the equipment manufacturer grouped with the NOVA software version 1.11, which in this context serves as an auxiliary tool for the tests. With this, it becomes substantial to understand the operation and to elaborate a manual aiming to facilitate and standardize the equipment operations. The entire study resulted in the elaboration of a guide that will assist in the instrument performance within the scope of the Universidade Federal Rural do Semi-árido (UFERSA) generating reliability in the analysis performed
Monografia
Keywords: Procedimento; Potenciostato; Polarização; Impedância; Procedure; Potentiostat; Polarization; Impedance; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA